Neural correlates of executive dysfunction in alcohol use disorder: preliminary evidence from 18F-FDG-PET - Arioli, Maria; Bossert, Irene; D’Ambrosio, Daniela; Manera, Marina; Andreolli, Elena Maria; Canessa, Nicola; Trifirò, Giuseppe (Frontiers in Psychology, 2025)
Neuroimaging studies have shown that cognitive impairments in Alcohol Use Disorder (AUD), particularly involving executive functions, reflect widespread structural and functional brain alterations. However, these findings mostly result from magnetic resonance imaging (MRI). To complement previous MRI findings with a more direct measure of brain metabolism, we therefore explored the neural bases of executive impairments in AUD using FDG-PET. Twenty-three AUD patients and 18 healthy controls underwent a neurocognitive assessment, and patients also an 18F-FDG-PET scan. Using as reference for brain metabolism a FDG-PET dataset of age-matched healthy controls, we assessed a relationship between executive impairment and regional hypometabolism in AUD patients, while also considering a possible moderating age effect. Compared with controls, AUD patients exhibited widespread hypometabolism in the anterior/midcingulate cortex, fronto-insular cortex, and medial precuneus, supporting the hypothesis that their impaired executive performance might reflect an altered transition from automatic to controlled processing. Patients’ worse executive performance reflected in higher metabolism in the midcingulate cortex and medial precuneus, suggesting a possible compensatory neural mechanism. This relationship was moderated by age in the right anterior insula, where the decrease of metabolism is steeper, in older patients, at the lowest level of cognitive performance. This finding suggests that an age-related decrease in the compensatory capacity of the insular node of the salience network might contribute to cognitive decline in older patients. While supporting the use of FDG-PET to improve the understanding of AUD-related cognitive decline, and differential diagnosis in older patients, these findings might help design personalized innovative treatment protocols.